Emitting-tunable Eu(2+/3+)-doped Ca(8−x)La(2+x) (PO4)6−x(SiO4)xO2 apatite phosphor for n-UV WLEDs with high-color-rendering. Issue 4 (12th January 2017) - Wei, Yi; Jia, Hui; Xiao, Hui; Shang, Meng Meng; Lin, Chun Che; Su, Chaochin; Chan, Ting-Shan; Li, Guo Gang; Lin, Jun
Abstract : A colorful phosphor [Ca8− x La2+ x (PO4 )6− x (SiO4 ) x O2 :Eu 2+ /Eu 3+ ] was designed by cosubstituting [Ca 2+ –P 5+ ] for [La 3+ –Si 4+ ] for pc-WLEDs with a high CRI. Abstract : Currently, developing single-phased white light phosphors based on a single-doped activator is an efficient approach to blends of bicolor/tricolor phosphors for realizing phosphor-converted white light emitting diodes (pc-WLEDs) with a high color rendering index (CRI) and low correlated color temperature (CCT). Here, we present high CRI ( R a = 93–95) and low CCT (3500–6000 K) white lights by cosubstituting [Ca 2+ –P 5+ ] for [La 3+ –Si 4+ ] in the solid solution Ca(8→2) La(2→8) (PO4 )6− x (SiO4 ) x O2 :Eu 2+ /Eu 3+ (CLPSO_Eu). The results are attributed to the presence of multi Ca 2+ sites due to possible mixing nanophases and the simultaneous occupancy of Ca 2+ and La 3+ sites by Eu, resulting in the mixing of blue (466 nm) and green emissions (540 nm) for Eu 2+, and red emission (613 nm) for Eu 3+, which were perfectly confirmed using X-ray Rietveld refinement, photoluminescence spectra and extended X-ray absorption fine structure. These findings not only imply that the as-prepared CLPSO_Eu are promising single-phased white light phosphor for near-UV based WLEDs but also offer a novel avenue to design high CRI white light phosphors based on a tunable Eu 2+ /Eu 3+ .